2022
DOI: 10.1002/rem.21706
|View full text |Cite
|
Sign up to set email alerts
|

PFAS Experts Symposium 2: PFAS Toxicology and Risk Assessment in 2021—Contemporary issues in human and ecological risk assessment of PFAS

Abstract: This paper summarizes key information on topics of contemporary interest in human and ecological per‐ and polyfluoroalkyl substance (PFAS) risk assessment, which were discussed at the PFAS Experts Symposium 2. For human health, the discussion focused on the toxicologic and epidemiologic endpoints and exposure assumptions that contribute to differences in PFAS regulatory criteria. For ecological risk, the discussion assessed the current state of the science available to support ecological screening levels and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Based on several recent epidemiology surveillance studies, no consistent evidence of an increased risk between PFAS exposure and neurotoxicity had been observed [ 90 , 91 ]. However, in-depth studies at cellular and molecular levels ( Table 2 ) have shown that PFAS possess the potential to trigger and/or participate in pathways that may lead to neurobehavioral disorders, such as ADHD, fetal congenital cerebral palsy, memory dysfunction, learning disorders, and intellectual disability.…”
Section: Polyfluoroalkyl Substancesmentioning
confidence: 99%
“…Based on several recent epidemiology surveillance studies, no consistent evidence of an increased risk between PFAS exposure and neurotoxicity had been observed [ 90 , 91 ]. However, in-depth studies at cellular and molecular levels ( Table 2 ) have shown that PFAS possess the potential to trigger and/or participate in pathways that may lead to neurobehavioral disorders, such as ADHD, fetal congenital cerebral palsy, memory dysfunction, learning disorders, and intellectual disability.…”
Section: Polyfluoroalkyl Substancesmentioning
confidence: 99%
“…The need for a comprehensive ecological risk assessment for PFAS calls for an improved understanding of their ecotoxicity. Several studies have concluded, however, that the current information on the ecotoxicity of PFAS is scattered, ambiguous, and strongly biased toward a limited spectrum of compounds and test organisms (ITRC, 2022; Van Keer et al, 2020; Zodrow et al, 2022). To address this knowledge gap, an analysis was conducted using data from studies spanning 2012 to 2022, focusing on algae, higher plants, fungi, amphibians, fish, insects, crustaceans, spiders, molluscs, worms, and other invertebrates.…”
Section: Ecotoxicity Of Pfasmentioning
confidence: 99%
“…90,91 PFAS also pose ecological risks through bioaccumulation, food chains, and toxicity in terrestrial and aquatic wildlife. 92…”
Section: Chemcomm Highlightmentioning
confidence: 99%